Self-Assembled Nanogels Based on Ionic Gelation of Natural Polysaccharides for Drug Delivery - Wang, Huimin; Deng, Hong; Gao, Menghan; Zhang, Weiqi (Frontiers in Bioengineering and Biotechnology, 2021)
The polysaccharides have been widely used as biomaterials in drug delivery, due to their excellent biocompatibility, ease for functionalization and intrinsic biological activities. Among the various polysaccharide-based biomaterials, the self-assembled polysaccharide nanogels featuring with facile preparation are attracting ever-growing interests in various biomedical applications. Specifically, nanogels derived from the self-assembly of natural polysaccharides well maintain both the physicochemical and biological properties of polysaccharides while avoiding the chemical modification or alteration of polysaccharides structure, representing a potent drug delivery system for disease management. In this review, the natural polysaccharides chitosan, alginate and hyaluronan for self-assembled nanogels construction as well as their advantages in drug delivery applications have been summarized. The residues such as amine, carboxyl and hydroxyl groups on these polysaccharides provide multiple sites for both ionic cross-linking and metal coordination, which greatly contribute to the formation of self-assembled nanogels as well as the drug loading, thus enable a wide biomedical application of polysaccharide nanogels especially for drug delivery. The future developments and considerations in the clinical translation of these self-assembled polysaccharide nanogels have also been discussed.